Comparison study towards an old Acehnese fara’idh table - Salmawaty Arif (Syiah Kuala University, 2011)
The paper aims to present the process of preliminary study on Acehnese manuscript about fara’idh. The script presented the law in the form of a compact table, written in Jawi script and Arabic. The research studied the table formation and filled it with the content of another fara’idh table from the current reference. This step was done to do the comparison of the two tables to get insights of the old table before further investigation about its mathematical properties. Previous investigation showed some differences in the writing of parts of the tables. This research continued to see the differences of the whole tables. Further purpose is to re implement the usage of the table in Acehnese daily use as well as broader advantage